SHADING EFFECTS ON GROWTH AND PARTITIONING OF PLANT BIOMASS IN PASPALUM CONJUGATUM BERG - I,B IPOR (SEAMEO BIOTROP, 1992)
Glasshouse studies were carried out to determine the effect of shading on the growth and partitioning of plant biomass in Paspalum conjugatum Berg. The invidual leaf rate expansion, final leaf are, specific leaf area, and the whole plant vegetative growth pattern, dry-matter production, leaf area as well as biomass partitioning were significantly influenced by shading. At the 75% level of shading, P. conjugatum produced the highest values of leaf weight ratio, specific leaf area and leaf area ratio. Individual leaf assessment revealed that shading significantly increased the final leaf area, duration of leaf expansion and specific leaf area.